Uniting Board to Bedside: The Use of Driver Diagrams in Quality Monitoring and Improvement at Trillium Health Centre - Patti Cochrane, Amir Ginzburg, Gary Spencer and Farah Marani (Healthcare Quarterly, 2011)
Boards of directors of healthcare organizations are increasingly being urged to extend their governance activities beyond financial matters to include the quality of patient care. Recently, Trillium Health Centre identified four big dot indicators and generated corollary driver diagrams aimed at helping its board understand and measure the organization's quality improvement plans, efforts and results. In addition to keeping board members up to date on these developments, the driver diagrams have supported quality improvements in their own right – for example, with hospital-acquired pressure ulcers – and have helped staff to focus and become more deeply engaged in Trillium's patient-centred quality improvement initiatives.
Keywords: Patti Cochrane, Amir Ginzburg, Gary Spencer, Farah Marani, governance, care quality, patient safety, measurement, reporting